A novel finding related to bulla and bleb formation in patients with primary spontaneous pneumothorax - Iyoda, Akira (BMC Pulm Med, 2021)
BACKGROUND: Spontaneous pneumothorax is a common problem globally. Bullas and blebs have been implicated in this problem, but the etiology of their formation is unknown. We aim to show the relation between a novel clinical finding, the pulmonary delayed inflation (PDI) sign, and the etiology of bulla and bleb formation in young patients. METHODS: We retrospectively analyzed data from 111 patients with pneumothorax and a control group of 27 patients. We evaluated the relation between the PDI sign and other clinical factors. RESULTS: The PDI sign was observed in 78 patients. Of these, 75 exhibited the PDI sign in only the upper lobe. Regardless of smoking status, patients 34 years of age or younger had a significantly higher incidence of the PDI sign than, patients 55 years of age or older and control patients. The inflation time in patients 34 years of age or younger, regardless of smoking status, was significantly longer than in patients 55 years of age or older and patients in the control group. There was no significant association between inflation time and the presence of asthma. CONCLUSIONS: The novel PDI sign is seen in patients 34 years of age or younger. Because this sign may indicate a peripheral bronchial abnormality and may be related to the formation of blebs and bullae in young patients with spontaneous pneumothorax, it is possible that it can be used to develop effective treatments for pneumothorax in young patients.